SISTEM INFORMASI ANALISIS AKUNTANSI PENJUALAN BERBASIS WEB PADA DJAROT CELL MENGGUNAKAN METODE TIME SERIES - Ulfanur Jannah (Jurnal Ilmiah Sistem Informasi, 2024)
Djarot Cell is a company that provides credit for all operators, electric credit and vouchers. Djarot Cell is located at JL. Lebo Islamic Boarding School RT/RW; 03/05 Gringsing. The Sales Information System at Djarot Cell is not yet equipped with a sales plan. The absence of sales planning for the future makes it difficult to determine future sales targets and the number of sales targets that have been achieved and the form of reports that are still manual makes it difficult for owners to see business developments. Because the condition of the Djarot Cell company is that sales data can fluctuate every month. Based on this research, the author created a Web-Based Sales Accounting Analysis Information System application on Djarot Cell using the Time Series Method. The author hopes that this sales accounting analysis information system can make it easier for owners to make decisions, especially for managing data more regularly which will influence the company's finances for the better and be able to determine and know the size of sales plans and sales that have been achieved in a certain period.